Recognition Functions of Pentameric C-Reactive Protein in Cardiovascular Disease. (18th May 2014) - Agrawal, Alok; Gang, Toh B.; Rusiñol, Antonio E.
Abstract : C-reactive protein (CRP) performs two recognition functions that are relevant to cardiovascular disease. First, in its native pentameric conformation, CRP recognizes molecules and cells with exposed phosphocholine (PCh) groups, such as microbial pathogens and damaged cells. PCh-containing ligand-bound CRP activates the complement system to destroy the ligand. Thus, the PCh-binding function of CRP is defensive if it occurs on foreign pathogens because it results in the killing of the pathogen via complement activation. On the other hand, the PCh-binding function of CRP is detrimental if it occurs on injured host cells because it causes more damage to the tissue via complement activation; this is how CRP worsens acute myocardial infarction and ischemia/reperfusion injury. Second, in its nonnative pentameric conformation, CRP also recognizes atherogenic low-density lipoprotein (LDL). Recent data suggest that the LDL-binding function of CRP is beneficial because it prevents formation of macrophage foam cells, attenuates inflammatory effects of LDL, inhibits LDL oxidation, and reduces proatherogenic effects of macrophages, raising the possibility that nonnative CRP may show atheroprotective effects in experimental animals. In conclusion, temporarily inhibiting the PCh-binding function of CRP along with facilitating localized presence of nonnative pentameric CRP could be a promising approach to treat atherosclerosis and myocardial infarction. There is no need to stop the biosynthesis of CRP.